Nekaf Mese ma Ansaof Mese sebagai Paradigma Teologi Kontekstual dalam Integrasi Mandat Ilahi dan Budaya: Kajian Teologis Matius 22:37–40 - Yunus Selan (SANCTUM DOMINE: JURNAL TEOLOGI, 2026)
This study addresses the gap between the teaching of love in Matthew 22:37–40 and the social practices of Christian communities that still reflect fragmentation between spiritual and social dimensions. In the context of the Atoen Pah Meto community, the philosophy of Nekaf Mese ma Ansaof Mese, which emphasizes unity of heart and action, has not been sufficiently examined as an integrative theological framework. In addition, studies of contextual theology in Indonesia remain limited in developing local culture as a hermeneutical medium that connects the divine and cultural mandates. This research aims to analyze this philosophy as a paradigm of contextual theology using a qualitative approach through literature study and contextual theological analysis based on the model of Stephen B. Bevans. The findings show that this philosophy represents the integration of vertical and horizontal love. The novelty lies in positioning local culture as a locus theologicus and an operational hermeneutical framework, contributing to global discourse on contextual theology.